The Synod of Bishops on the Family. Some marginal Canonical Notes - Díaz Moreno, S.J., José María (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
From a canonical perspective, the author offers some reflections based on the documents of the Extraordinary General Assembly of the Synod of Bishops as well as the preparatory documents for the XIV Ordinary General Assembly. The author points out the deep connection between the two Assemblies, and deepens into topics such as the understanding of the family as a domestic Church, the civil marriage of Catholic people, the reform of the procedure to declare the nullity of the marriage, the shorter process before the Bishop, the lack of faith of the spouses, the brevity of married life.